Formulation and Characterization of Nanoemulsion Incorporating Chamomilla recutita L. Extract Stabilized with Hyaluronic Acid - Getulio Capello Tominc; Mariana Dalmagro; Elton da Cruz Alves Pereira; Maisa Steffani Adamczuk; Francieli Gesleine Capote Bonato; Rafael Menck de Almeida; Ricardo Schneider; Melyssa Fernanda Norman Negri; Daniela Dib Gonçalves; Jaqueline Hoscheid (MDPI AG, 2024)
Skin lesions are an important health concern, exposing the body to infection risks. Utilizing natural products containing chamomile (Chamomilla recutita L.) holds promise for curative purposes. Additionally, hyaluronic acid (HA), an active ingredient known for its tissue regeneration capacity, can expedite healing. In this study, we prepared and characterized an extract of C. recutita and integrated it into a nanoemulsion system stabilized with HA, aiming at harnessing its healing potential. We assessed the impact of alcoholic strength on flavonoid extraction and chemically characterized the extract using UHPLC/MS while quantifying its antioxidant and antimicrobial capacity. We developed a nanoemulsion loaded with C. recutita extract and evaluated the effect of HA stabilization on pH, droplet size, polydispersity index (PDI), zeta potential, and viscosity. Results indicated that 70% hydroalcoholic extraction yielded a higher flavonoid content. The extract exhibited antioxidant capacity in vitro, a desirable trait for skin regeneration, and demonstrated efficacy against key microbial strains (Staphylococcus aureus, Streptococcus pyogenes, Escherichia coli, and Pseudomonas aeruginosa) associated with skin colonization and infections. Flavonoids spireoside and apiin emerged as the most abundant bioactives. The addition of HA led to increased viscosity while maintaining a suitable pH for topical application. Zeta potential, droplet size, and PDI met acceptable criteria. Moreover, incorporating C. recutita extract into the nanoemulsion enhanced its antimicrobial effect. Hence, the nanoemulsion system loaded with C. recutita and HA stabilization exhibits favorable characteristics for topical application, showing promise in aiding the healing processes.